Absolute chronology of the early settlements of the Acarí valley - Valdez, Lidio M. (2021)
Archaeological research carried out in the Acarí Valley enables us discussing the dynamics of the early occupations in this valley regarded as the southern boundary of the archaeological-cultural region known as the Peruvian south coast. The foundation of the complex cultural development of Acarí can be found at the Hacha site that belongs to the Initial Period. Material evidence and several radiocarbon dates indicate that Hacha was occupied for a long time, from as early as 3398 to 2737 cal BP. Subsequently, new human settlements seem to have been established in the vicinity of Hacha, following which the site was finally abandoned. At the same time, new settlements were established in other parts of the valley and became the foundation for a series of large settlements that flourished during the early phases of the Early Intermediate Period. Starting with Hacha, the pottery developed in this valley exhibits continuity, the same that extends until the middle of the Early Intermediate Period. Sometime late during the Early Horizon, the inhabitants of Acarí were in contact with the peoples of the valleys found further to the north, which allowed the arrival of some northern artifacts. It appears that the Paracas or Nasca never established themselves in this valley. Thus, starting late during the Early Horizon, the peoples of Acarí maintained close and continuous relationship with the various cultural traditions that flourished in time and space in the valleys further to the north. This relationship not only made of Acarí the last valley of the south coast to maintain its northern orientation and association, but also this orientation continued for a long time, even until the Inka times.